Solar energy fruits and vegetables drying equipment - QIU QIUYAN; GAN WEIPING; MA ZHAOJIAN; WEI GUANCHUAN; NONG ZHILING; LU JUNXING (2015)
Solar energy fruits and vegetables drying equipment, including photovoltaic solar panel, battery, solar energy intelligent control ware and fruits and vegetables drying cabinet, photovoltaic solar panel's positive negative pole passes through being connected of wire and battery, and the battery is connected afterwards with solar energy intelligent control ware, receives the fruits and vegetables drying cabinet, the fruits and vegetables drying cabinet divide into more than the one deck, each layer box is internal installs independent zone of heating, every zone of heating all is equipped with heating platform and heating coil, heating coil passes the tank wall respectively and is connected with solar energy intelligent control ware. The utility model provides a solar energy fruits and vegetables drying equipment combines solar PV cells, and through the dry fruits and vegetables of heating coil, solve fruits and vegetables tradition hot air drying quality is low, the pollution is big, and the dry energy consumption of vacuum freezing is high, the problem of inefficiency.